PENGARUH HEDONIC MOTIVATION, INFORMATION, TRUST, DAN PRICE TERHADAP NIAT PEMBELIAN ONLINE PADA GENERASI X DI JAKARTA - AURELSHA, TARISHA; PRASASTYO, KLEMENS WEDANAJI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
The main objective of this research is to determine the impacts of hedonic motivation, access to online information, online trust, and online price towards online purchase intention when shopping online on Generation X in Jakarta. This research used descriptive and causality research design, using 5-point Likert scale to measure variables. This research applied non-probability sampling and purposive sampling on 245 respondents and used Structural Equation Modeling (SEM) with WarpPLS 7.0 as its analytics tool.The result of this research indicates that hedonic motivation, access to online information, and online trust give positive and significant impacts towards online purchase intention. Meanwhile, online price gives positive and not significant impacts towards online purchase intention.